First episode rapid early intervention for eating disorders: A two‐year follow‐up. Issue 1 (15th October 2019) - Fukutomi, Akira; Austin, Amelia; McClelland, Jessica; Brown, Amy; Glennon, Danielle; Mountford, Victoria; Grant, Nina; Allen, Karina; Schmidt, Ulrike
Abstract: Aim: We describe 2‐year outcomes of a novel first episode early intervention service for young adults with a recent onset eating disorder (FREED). Outcomes in FREED patients with anorexia nervosa (AN) were compared with those from patients previously seen in our service [treatment as usual (TAU) cohort], matched for age, illness duration and diagnosis. Methods: Electronic case records of FREED‐AN (n = 22) and TAU‐AN patients (n = 35) were examined to identify service utilisation and clinical outcomes over 24 months. Results: Outpatient service utilisation was similar in both groups, but FREED‐AN patients needed intensive (in‐ or day‐patient) treatment less frequently than TAU‐AN (23% vs 32%). FREED‐AN patients had a higher estimated mean body mass index [19.2 kg/m 2 ; 95% CI (18.21, 20.16)] than TAU patients [18.0 kg/m 2 ; 95% CI (16.90, 19.15)] at last contact. Conclusion: Introduction of FREED led to a more complete recovery in patients with AN at 24 months.